Stress field and active faults in the orogenic front of the Andes in the Malargüe fold-and-thrust belt (35°–36°S) - Mescua, Jose Francisco (2019)
We integrate field and wellbore data to discuss the stress field in the frontal sector of the Malargüe fold-and-thrust belt (Andes of Argentina). Surface observations indicate N-S thrusts and NW to WNW and ESE strike-slip faults are active in the study area. Inversion of fault kinematic indicators, combined with borehole breakout data and a mini-frac test within the study area, constrain the Quaternary to recent stress state, which is characterized by a subhorizontal, E-W oriented maximum stress, and by intermediate and minimum stresses with similar magnitudes that are locally interchanged, producing a setting in which reverse and strike-slip faults are alternatively active. The implications of the recognized structures for earthquake hazard are examined.